Evolution of healthcare provider payment mechanisms - V. V. Omelyanovskiy; N. N. Sisigina; V. K. Fedyaeva; N. Z. Musina (IRBIS LLC, 2020)
Methods of payment to care providers constitute an essential part of the healthcare financing system; these mechanisms determine the motivation of service providers. Throughout the history of public health care, the payment methods have been gradually improved so to stimulate the providers to best match the societal demands (greater access to health services, cost reduction, and better quality) and prevent "moral hazards". As a result, the most advanced healthcare systems have stopped paying simply for service volume and rigorously restraining the costs. Instead, the updated system is based on the integrated payments combining the elements of cost control with the stimuli that promote a high quality and better access to healthcare service. At present, the new payment mechanisms aiming at improving the long-term treatment outcomes (life expectancy and quality of life) are available. The care provider payment system existing in Russia, by large, corresponds to the best international practices as far as the hospital care is concerned. However, the payment arrangements in the primary care network still lag behind the international standards. To improve the situation, quality indicators should be included in payments for primary care services.